Kinetic Model for Describing Oxygen Fluxes Across the Sediment-water Interface
The oxygen uptake rate of coastal sediments has been investigated. The method which has been used for measuring the oxygen uptake of sediment consisted in transferring undisturbed sediment cores to laboratory and measuring oxygen depletion in overlying water by using stirring oxygen probe (YSI Model 5739). Changes in amount of dissolved oxygen over the sediment cores can be calculated as oxygen fluxes, and expressed as mg O2 m-2 hr-1. The oxygen fluxes across the sediment-water interface was noticed to be dependent upon oxygen concentrations of the overlying water. By modifying Fick’s Law of diffusive fluxes, one dimension diffusion of dissolved oxygen in the sediment has been described and the mathematical approximation of total benthal oxygen uptake (BOU) was proposed to be BOU = F + . In the case of the benthal sediment in which contained only a few macroinvertebrates, a linear relationship can be obtained when the square of BOU rates were plotted against the oxygen concentrations of overlying water. It seemed that differences in slopes and intercept constants of such regression lines implied the differences in relative importances of microbial and inorganic oxidation reaction that varied seasonally and depended on sampling locations of benthal sediments. The expression of respiratory activity of active macroinvertebrates was also discussed. , number=1, journal=Agriculture and Natural Resources, author=Meksumpun, Charumas, year=2001, month=Mar., pages=74–84